Intervensi Dini Bersumberdaya Keluarga pada Perkembangan Bahasa Anak Disabilitas Intelektual - Khibdziyah, Lailatul; Sukmawati, Bhennita; Nurhadiyati, Arifah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to describe the form of family-based early intervention on the language development of children with intellectual disabilities at Muhammadiyah 1 Elementary School in Jember. This study used a qualitative approach with a case study method, with one child with moderate intellectual disabilities at Muhammadiyah 1 Elementary School in Jember and his parents as subjects. The results showed that active parental involvement through family-based interventions using smartcards had a positive impact on children's language skills, particularly in combining words into simple sentences. The use of smartcards helped children focus better, become more interested in learning activities, and understand the relationship between words and images concretely. Children showed progress from simply saying words one by one to being able to put two or three words together into meaningful sentences. Furthermore, the learning environment at home became more enjoyable and interactive, strengthening the emotional bond between parents and children. In conclusion, family-based early intervention supported by visual media such as smartcards is efficacious in improving the language skills of children with intellectual disabilities. This approach not only enhances linguistic skills but also strengthens emotional interactions within the family, providing an alternative, applicable, and home-based inclusive learning strategy that is easy for parents to implement. Keywords: Early Intervention; Smartcards; Intellectual Disability